Evaluation of GPR capabilities in the study of seismogenic faulting and deformation in the bottom sediments of Lake Upoloksha (northeast of the Fennoscandian shield) - A. I. Rodionov; S. B. Nikolaeva; P. A. Ryazantsev (Геодинамика и тектонофизика)
The article describes the experience of using the GPR method to study the bottom sediments of Lake Upoloksha located in the Kola Peninsula, Russia. Such sediments are viewed as good archives of various Holocene geodynamic processes, including tectonic and paleoseismic events. This small lake is located in the zone of the active NW-striking lineament, which length is more than 20 km. A series of åsars (eskers) stretches along the lineament. In the previous studies, the bottom sediments of the lake were investigated by geological methods, including core sampling, lithological and micro-palaeontological analysis of sediments. The studies have revealed a horizon which features are indicative of catastrophic changes in the sedimentation conditions due to a single impact. Our study aimed at evaluating the level of informativeness of the GPR method for detecting disturbances in the bottom sediments and new paleoseismic dislocations. The study referred to the hypothesis of the distribution of seismic foci in the Kola Peninsula in the Holocene. A ground-penetrating radar OKO-2 and an antenna unit (150 MHz) were used to survey of Lake Upoloksha in detail. The positions of the main stratigraphic horizons of the bottom sediments were clarified, and their thicknesses were measured more precisely. The GPR measurement error in comparison to the drilling data did not exceed ±0.2 m, which corresponds to the resolution of the antenna used in the survey. The GPR data confirmed the existence of seismic dislocations identified by the geological methods and discovered new zones of displacement and deformation in the organogenic and mineral bottom sediments. The survey detected vertical displacements, which amplitudes vary from 1.3 to 1.7 m, and landslides caused by seismogravitational rock collapse. Based on the GPR data, a bathymetric map was constructed. It shows the positions of the two basins of Lake Upoloksha. The survey provided the basis for a model showing the isosurface of the top of the mineragenous sequence. In the central part of the mineral-base model, there is a series of individual stepwise blocks of the sublatitudinal strike, which result from seismic movements. The GPR survey of Lake Upoloksha demonstrates that the GPR method can be successfully applied to estimate the mineral and organogenic parts of the bottom sediments, study their lithostratigraphic features, and detect changes in the structure of the bottom sediments. Based on the GPR data, it becomes possible to map even the small-scale disturbances.